2013
DOI: 10.1097/jsm.0b013e3182694870
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Injuries in Contact Flag Football

Abstract: Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på journals.lww.com: http://dx.doi.org/10.1097/JSM.0b013e3182694870 This is the final text version of the article, and it may contain minor differences from the journal's pdf version. The original publication is available at journals.lww.com: http://dx.doi.org/10.1097/JSM.0b013e3182694870 Main Outcome Measures: All time-loss injuries sustained in game sessions were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Current BAFA policy advises that "clubs must ensure that they have adequate first aid cover available for all practice sessions where contact will take place, " yet what determines "adequate" is unclear. Furthermore, the policy does not stipulate whether this refers to both flag-football and tackle football, as concussion occurs in both versions of the game (Kaplan et al, 2013;Prien et al, 2018). Thus, current "policy" may be deemed a haphazard approach to medical cover than outline true policy directives.…”
Section: Discussionmentioning
confidence: 99%
“…Current BAFA policy advises that "clubs must ensure that they have adequate first aid cover available for all practice sessions where contact will take place, " yet what determines "adequate" is unclear. Furthermore, the policy does not stipulate whether this refers to both flag-football and tackle football, as concussion occurs in both versions of the game (Kaplan et al, 2013;Prien et al, 2018). Thus, current "policy" may be deemed a haphazard approach to medical cover than outline true policy directives.…”
Section: Discussionmentioning
confidence: 99%
“…Direct trauma was responsible for the vast majority of injuries (ranging between 64 and 75 %). In the latest of these three studies, conducted by the authors of the present manuscript, forty per cent of the hand/finger injuries were reported as a direct result of fingers being caught in the opposing player's pants [17]. Almost all players in this study wore pants with side pockets and refrained from playing with mouth guards, despite evidence that they have been shown to prevent oral and tongue injuries and that they might reduce the severity of concussions [4,6,21].…”
Section: Introductionmentioning
confidence: 53%
“…Three previously published epidemiological studies reported on injuries in flag football [3,5,17]. All three reported a high percentage of injuries to the fingers/wrist (ranging between 16 and 34 %), the knee (ranging between 11 and 16 %), the ankle (ranging between 8 and 12 %), the face and head (18 %) and the shoulder (9 %).…”
Section: Introductionmentioning
confidence: 98%
“…However, the reports that were found were diverse. : from kickboxing and TBI in Qatar and Turkey (Slimani et al, 2017;Tanrivedi et al, 2007), fishing and aerial sport injuries as well as boxing related injuries in Turkey (Aydin, 2019;Cevik et al, 2016;Tanrivedi et al, 2008), to contact football and other team balls in Iran and Israel (Kordi et al, 2013;Kaplan et al, 2013), to new data on E-Biking with resulting serious injuries in Israel and Iran (Gross et al, 2018;Vahdati et al, 2016), rollover crashes as well as injuries related to Taekwondo and Karate in Iran (Anarkooli et al, 2017;Ziaee et al, 2010;Halabchi et al, 2007) and lastly camel jockeying injury in United Arab Emirates (UAE) (Abu-Zidan et al, 2012). Many countries focused on extremity injuries and were keen on detailing those injuries specifically; while data regarding head injury on the other hand was relatively sparse.…”
Section: Resultsmentioning
confidence: 99%